Propagation of Grapefruit (Citrus Paradisi Macf) by Shoot Tip Micrografting - M. A. Ali, Hamaraie; M. Elamin, Osman; A. Ali, Mohamed (Gezira Journal of Agricultural Science; Vol 2 No 1 (2004), 2021)
This study was conducted to develop an in vitro technique for micrografting of grapefruit on sour orange rootstock during August, 2001 to May, 2002. The best in vitro germination of rootstock seed was obtained when both seed coats (hard and soft) were removed before in vitro culturing on a nutrient medium. The success of micrografting was affected by the age of rootstock seedling, light incubation conditions, source and method of placement of meristem tips and concentration of sucrose in the nutrient medium. High frequency of successful micrografts was obtained when the rootstock seedlings were germinated under darkness till the age of two weeks and then incubated in the same condition for two to three weeks after grafting. Plants grown in the greenhouse were the best source for meristem tips. Placement of scion on an inverted T incision at the point of decapitation was found to be the most suitable method of micrografting. The frequency of successful micro. grafts improved significantly when Murashige and Skoog medium was supplemented with 7.5% sucrose compared with normal sucrose concentration (3%).. INTRODUCTION